2011
DOI: 10.1038/cr.2011.28
|View full text |Cite
|
Sign up to set email alerts
|

Reprogramming to pluripotency: stepwise resetting of the epigenetic landscape

Abstract: In 2006, the "wall came down" that limited the experimental conversion of differentiated cells into the pluripotent state. In a landmark report, Shinya Yamanaka's group described that a handful of transcription factors (Oct4, Sox2, Klf4 and c-Myc) can convert a differentiated cell back to pluripotency over the course of a few weeks, thus reprograming them into induced pluripotent stem (iPS) cells. The birth of iPS cells started off a rush among researchers to increase the efficiency of the reprogramming proces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
115
0
8

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 165 publications
(124 citation statements)
references
References 133 publications
(259 reference statements)
1
115
0
8
Order By: Relevance
“…Nuclear reprogramming induced by trans cription factors resets the epigenetic landmarks, which leads to the global reversion of the somatic epigenomes to an ESC like state (Maherali et al, 2007;Papp and Plath, 2011). However, the mechanisms involved, particu larly the posttranslational interactions and modifications, remain undetermined.…”
mentioning
confidence: 99%
“…Nuclear reprogramming induced by trans cription factors resets the epigenetic landmarks, which leads to the global reversion of the somatic epigenomes to an ESC like state (Maherali et al, 2007;Papp and Plath, 2011). However, the mechanisms involved, particu larly the posttranslational interactions and modifications, remain undetermined.…”
mentioning
confidence: 99%
“…Mechanistically, this group have shown that FGF2 promotes the early stages of reprogramming through accelerating cell proliferation, facilitating MET and eliminating extracellular collagens. In addition to an increased proliferation rate, the minority of cells that undergo successful reprogramming also exhibit resistance to apoptosis and senescence, by transgene expression [56] . Recent studies have shown that miR-302 expression allows cells to overcome reprogramminginduced senescence [62] and that silencing of the INK4/ ARF locus is also likely to be involved, since INK4/ARF blockade improves reprogramming efficiency [63,64] .…”
mentioning
confidence: 99%
“…The reprogramming process demonstrates the profound flexibility of the mammalian epigenome, indicating modulators of epigenome are critically involved in iPSC generation [55] . Accordingly, small molecules that directly modulate the epigenetic enzymes or mechanisms, which in turn change DNA or histone modifications, have been demonstrated to affect reprogramming.…”
Section: Epigenetic Modifiersmentioning
confidence: 99%